Hubungan Psikologi dan Design Thinking dalam Pengalaman Pembelajaran MOOC - Mafanda Naura Nasiwa; Nuzsep Almigo (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Massive Open Online Courses (MOOCs) have become an increasingly popular form of digital learning, offering flexibility and broad access to educational materials. However, the effectiveness of learning in MOOCs depends not only on content and technology but also on the psychological aspects of participants and the pedagogical approaches used. This report aims to analyze the relationship between psychology and Design Thinking in the MOOC learning experience. Through a descriptive qualitative method, it was found that psychological factors such as motivation, emotion, self-efficacy, and self-regulation play a crucial role in determining participant engagement and success. Meanwhile, the application of Design Thinking stages (empathize, define, ideate, prototype, and test) can enhance creativity, problem-solving, and critical reflection. The study results indicate that integrating psychological approaches and Design Thinking creates a more holistic, interactive, and meaningful learning experience, encouraging participants to become independent, innovative, and adaptive learners. Recommendations are provided for participants, MOOC organizers, and educational institutions to optimize online learning design by considering psychological aspects and design thinking methods.